A study on tool deflection during deep pocketing cycle - Zikrulhakim, Muhd Zahid (2013)
Tool deflection during deep pocketing cycle will cause tapper in mould and die. This problem can cause defect on final product and also increases cost and time wasting in manufacturing process. This study basically shows a detailed study to overcome tapper problem in deep pocket. Dimensional accuracy due to tapper problem was analyzed in order to obtain optimum cutting parameters. The pocket part was drawn by using CATIA software. The data collected during experiment was analyzed using signal to noise ratio through Minitab software. From the analysis, it was found that depth of cut has gives the most effect on tapper problem, followed by feed rate and spindle speed. From the result, it is shown that level 1 of depth of cut which is 0.3mm, level 1 of feed rate which is 64mm and level 2 of spindle speed which is 1280rpm was the best cutting parameter. Hence, from these cutting parameters, the tapper problem cause by tool deflection during deep pocketing cycle can be overcome.